2017
DOI: 10.1002/2016jd025541
|View full text |Cite
|
Sign up to set email alerts
|

Evolution of trace elements in the planetary boundary layer in southern China: Effects of dust storms and aerosol‐cloud interactions

Abstract: Aerosols and cloud water were analyzed at a mountaintop in the planetary boundary layer in southern China during March–May 2009, when two Asian dust storms occurred, to investigate the effects of aerosol‐cloud interactions (ACIs) on chemical evolution of atmospheric trace elements. Fe, Al, and Zn predominated in both coarse and fine aerosols, followed by high concentrations of toxic Pb, As, and Cd. Most of these aerosol trace elements, which were affected by dust storms, exhibited various increases in concentr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
24
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(26 citation statements)
references
References 57 publications
(108 reference statements)
2
24
0
Order By: Relevance
“…The non-and semi-volatile species in cloud water at Mt. TMS including water-soluble ions, DOC, carboxylic acids and trace metals were inversely related to LWC in the power functions due to dilution effects, which have been widely observed in previous studies Li et al, 2017). Similar inverse-power relationships of water-soluble ions, DOC and carboxylic acids with pH were also found.…”
Section: Relationship Of Cloud Water Composition With Lwc and Phsupporting
confidence: 80%
See 1 more Smart Citation
“…The non-and semi-volatile species in cloud water at Mt. TMS including water-soluble ions, DOC, carboxylic acids and trace metals were inversely related to LWC in the power functions due to dilution effects, which have been widely observed in previous studies Li et al, 2017). Similar inverse-power relationships of water-soluble ions, DOC and carboxylic acids with pH were also found.…”
Section: Relationship Of Cloud Water Composition With Lwc and Phsupporting
confidence: 80%
“…TMS (Lam et al, 2013), as different precursors could lead to different yields of glyoxal and methylglyoxal (Ervens et al, 2011). Aluminium (131.9 μg L -1 ) dominated the cloud water trace metals, of which the concentration was comparable to that measured at other mountain sites in China (Li et al, 2017). Abundant transition metals Fe (50.6 μg L -1 ), Cu (10.0 μg L -1 ) and Mn (5.9 μg L -1 ), which played important roles in the heterogeneous catalytical formation of sulfate (Harris et al, 2013), were also found.…”
Section: Overview Of Chemical Composition Of Cloud Watermentioning
confidence: 73%
“…At Mount Tai in northern China, a high concentration of Ca 2+ in cloud or fog water was mainly attributed to a sandstorm event during the spring season . At Mount Heng in southern China, the abundant crust-related elements (e.g., Al) observed in cloud water is due to Asian dust storms that occurred in March-May (Li et al, 2017). Based on the backward trajectory, the site was unlikely affected by sandstorm source in northwestern China during the cloud events.…”
Section: The Chemical Characterization Of Cloud Droplet Residuesmentioning
confidence: 99%
“…The model analysis showed that the formation of dust-nitrate occurred over the Yellow Sea and East China Sea before arriving in Japan. The mid-March episode was studied with the on-line coupled Weather Research and Forecasting-Chemistry (WRF-Chem) model over the Nanjing area focusing on the interactions between the dust load with the photochemistry [137]. Combined with observational data, the WRF-chem model has been recently used in a recent study [138] They show the dust plume located in the altitudes ranging from 1 km to 7 km over the source region, then ascended to 2-9 km over the Pacific Ocean.…”
Section: Dust Outbreaks Over Chinamentioning
confidence: 99%